Metabolic and neuromuscular adaptations to endurance training in professional cyclists: A longitudinal study - Lucia, A.; Hoyos, J.; Pardo, J.; Chicharro, J. L. (Japanese Journal of Physiology, 2000)
The aim of this longitudinal study was to analyze the changes in several metabolic and neuromuscular variables in response to endurance training during three defined periods of a full sports season (rest, precompetition and competition). The study population was formed by thirteen professional cyclists (age +/- SEM: 24 +/- 1 years; mean V(O2 max) approximately 74 ml kg(-1) min(-1)). In each testing session, subjects performed a ramp test until exhaustion on a cycle ergometer (workload increases of 25 W min(-1)). The following variables were recorded every 100 W until the tests: oxygen consumption (V(O2) in l min(-1)), respiratory exchange ratio (RER in V(CO2) V(O2)(-1)) and blood lactate, pH and bicarbonate concentration [HCO(3)(-)]. Surface electromyography (EMG) recordings were also obtained from the vastus lateralis to determine the variables: root mean square voltage (rms-EMG) and mean power frequency (MPF). RER and lactate values both showed a decrease (p < 0.05) throughout the season at exercise intensities corresponding to submaximal workloads. In contrast, no significant differences were found in mean pH or [HCO(3)(-)]. Finally, rms-EMG tended to increase during the season, with significant differences (p < 0.05) observed mainly between the competition and rest periods at most workloads. In contrast, precompetition MPF values increased (p < 0.05) with respect to resting values at most submaximal workloads but fell (p < 0.05) during the competition period. Our findings suggest that endurance conditioning induces the following general adaptations in elite athletes: (1) lower circulating lactate and increased reliance on aerobic metabolism at a given submaximal intensity, and possibly (2) an enhanced recruitment of motor units in active muscles, as suggested by rms-EMG data.